PENINGKATAN KUALITAS DOSEN MELALUI IMPLEMENTASI REGULASI BEBAN TUGAS DOSEN - Dharman Gunawan, I Gede (LPM IHDN Denpasar, 2015)
Lecturer is the spearhead and the motor institution of higher education institutions to carry out activities Tridharma. As professionals, lecturersdemanded shopped constantly innovative and creative efforts to improve its quality in the field of science which they are. Lecturer is not only a professional educator at the, but also a. The principal tasks of lecturers in the faculty taskload regulation covering the fields of, research and community. Besides the main task of the lecturer also has another, namely academic and professional development and participation in higher education. So with the improvement of the quality of lecturers through the implementation of regulatory workload may also increase the welfare of the faculty lecturers.